Detection method for corrosion-resistant titanium alloy surface passive film structure

By using the variable-energy XPS testing method to adjust the photoelectron energy parameters and signal intensity analysis, the problem of non-destructive testing of nanoscale passivation film structures on titanium alloy surfaces was solved, and highly accurate characterization of film structures was achieved.

CN121499573APending Publication Date: 2026-02-10CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511699236.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-19
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing technologies struggle to accurately detect the nanoscale passivation film structure on titanium alloy surfaces without damage, and artifacts caused by inert gas ion etching affect detection accuracy.

Method used

The variable energy XPS test method was used to determine the passivation film structure on the titanium alloy surface by adjusting the photoelectron energy parameters and combining photoelectron spectroscopy, peak fitting and signal intensity analysis, without the need for inert gas etching.

Benefits of technology

This method enables non-destructive testing of passivation film structures on titanium alloy surfaces, improving the accuracy and applicability of test results, especially for characterizing films ≤20nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121499573A_ABST
    Figure CN121499573A_ABST
Patent Text Reader

Abstract

The invention provides a method for detecting a passivation film structure on the surface of a corrosion-resistant titanium alloy, which comprises the following steps of: performing X-ray photoelectron spectroscopy test on a sample by a method of changing energy, performing at least twice test to obtain a full spectrum and a spectrum of Ti, O and C, performing charge correction on the peak position of the C element, and performing peak-dividing fitting by adopting an element high-resolution spectrum to obtain the passivation film structure on the surface of the corrosion-resistant titanium alloy. And when the processed result meets the condition that only the photoelectron signal of the passive film is received at least once and the photoelectron signal from the titanium alloy matrix is received at least once in the test, outputting the structure of the passive film on the surface of the sample according to the signal intensity in the data processing and analysis result. Ion etching sputtering is not used in the XPS test process, the illusion generated by titanium ion reduction caused by argon ion etching in a conventional XPS etching-layer-by-layer stripping method is avoided, data obtained through analysis are more accurate, the detection method is a nondestructive detection method, no damage is caused to a film layer, and the detection accuracy is improved. And the accuracy of the detection result is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofilm testing technology for metallic material surfaces, and more specifically, to a method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys. Background Technology

[0002] Titanium alloys, renowned as "marine metals" due to their dense, nanoscale passivation film, exhibit excellent corrosion resistance and have become the preferred material for many marine equipment. However, some extreme marine service environments can cause titanium alloys to corrode and fail; this corrosion is typically closely related to the failure of their surface passivation film. To further expand the application scenarios of titanium alloys in marine engineering and clarify their safe service range, it is necessary to further understand the passivation film states formed by titanium alloys under complex external environments, elucidate the formation and evolution laws of titanium alloy passivation films in marine corrosive environments, and thus guide the application evaluation of titanium alloys. Therefore, the structural characterization of the nanoscale passivation film on the surface of titanium alloys is of great significance for optimizing and evaluating the corrosion protection performance of materials, and consequently guiding process optimization and maintenance.

[0003] For characterizing passivation film structures, cross-sectional FIB-SEM / TEM, XRD, and XPS are commonly used methods. Cross-sectional SEM / TEM combined with energy dispersive spectroscopy can detect film thickness and elemental composition. TEM can also determine the crystal structure of well-crystallized films. However, passivation films on titanium alloy surfaces are generally at the nanometer scale (≤20nm), and the resolution accuracy of SEM cannot meet the characterization requirements of titanium alloy passivation films. Once the passivation film exhibits an amorphous structure, the diffraction patterns of transmission electron microscopy cannot characterize the crystal structure of the passivation film. FIB-TEM is complex to operate and is somewhat destructive to the sample. XRD can characterize the crystal structure of materials, but it cannot characterize titanium alloy passivation films ≤20nm with partial amorphous structures (long-range disorder), as the weak signal can mask the film information from the metal substrate.

[0004] Patent CN116165234A discloses a method for detecting the SEI film of lithium-ion batteries using XPS. This method utilizes XPS argon ions to etch a silica coating of a predetermined thickness onto a standard sample under set operating parameters. The etching rate is calculated using the first etching time and the set thickness. Then, under the same operating parameters, the SEI film on a sample is etched, and the thickness of the SEI film is determined using the etching rate and the second etching time. This patented method, by using XPS argon ion etching of the sample to be tested, can determine the SEI film thickness simultaneously with component analysis, achieving nanoscale analysis. By obtaining the etching rate from the silica coating on the standard sample and the second etching time from the SEI film on the sample, the thickness of the SEI film can be easily calculated. XPS characterization testing technology is a testing method that uses X-rays to excite electrons in the inner-shell orbitals of atoms, derives the binding energy of the corresponding orbitals by measuring the photoelectron kinetic energy, and determines the type of excited atom and the chemical state of the element by the binding energy. In existing XPS film structure testing, the film structure is usually reconstructed by etching with inert gas ions, peeling off and collecting layer by layer. However, titanium alloys are more sensitive to inert gas ions such as argon ions. After etching, high-valence titanium ions are easily reduced, causing experimental artifacts and leading to incorrect experimental conclusions. Therefore, it cannot be used for the detection and characterization of passivation film structures on titanium alloy surfaces. Summary of the Invention

[0005] In view of this, the present invention aims to provide a method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys, enabling accurate detection of the passivation film structure of corrosion-resistant titanium alloys without damage.

[0006] This invention discloses a method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys, comprising the following steps:

[0007] Step S1: Sample preparation and installation;

[0008] Step S2: Experimental testing. By adjusting the photoelectron energy parameters through the target material parameters, X-ray photoelectron spectroscopy is performed on the sample, and at least the full spectrum, Ti, O and C spectra are obtained.

[0009] Step S3: Data processing and analysis, charge correction of the peak position of element C, and peak fitting using high-resolution elemental spectra; determine whether the number of tests is greater than 1. If yes, proceed to step S4; otherwise, proceed to step S5.

[0010] Step S4: Determine whether the data processing results of all current test counts meet the preset conditions. If yes, proceed to step S8; otherwise, proceed to step S5.

[0011] Step S5: Determine whether the data processing results of all current test counts meet the first preset state. If yes, proceed to step S6; otherwise, proceed to step S7.

[0012] Step S6: Return to step S2 for the same region and increase the photoelectron energy;

[0013] Step S7: Return to step S2 for the same region and reduce the photoelectron energy;

[0014] Step S8: Obtain the passivation film structure on the sample surface based on the signal intensity in the data processing and analysis results.

[0015] Furthermore, the preset conditions in step S4 refer to:

[0016] In at least one test, a photoelectron signal was received only from the passivation film, and in at least one test, a photoelectron signal was received from the titanium alloy substrate.

[0017] Furthermore, in step S5, the first preset state refers to:

[0018] Data processing results for all tests indicate that only photoelectron signals were received from the passivation film.

[0019] Furthermore, the photoelectron energies used in the tests ranged from 1200 to 5420 eV.

[0020] Furthermore, step S1 includes:

[0021] Step S11: Mark the side to be tested according to XPS requirements and process the test sample;

[0022] Step S12: Fix the test sample on the sample stage and keep the test sample in contact with the sample stage.

[0023] Furthermore, in step S12, the test sample is attached to the sample stage using conductive carbon-based tape, and the conductive carbon-based tape covers the edge of the test surface on the test sample.

[0024] The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloy as described in claim 1 is characterized in that the power acquisition range during testing is 50~600W.

[0025] Furthermore, the sampling step size during testing was 0.05~0.2eV.

[0026] Furthermore, the number of spectral samplings per test ranges from 3 to 30.

[0027] Compared with existing technologies, the detection method for passivation film structure on corrosion-resistant titanium alloy surfaces described in this invention has the following advantages:

[0028] (1) No inert gas is used in the XPS test of this invention, which avoids the artifact caused by titanium ion reduction due to argon ion etching in the conventional XPS etching-layer-by-layer peeling method, and the data obtained by analysis is more accurate;

[0029] (2) The detection method provided by the present invention is a non-destructive testing method. Compared with the existing detection methods such as cross-sectional observation and etching, it does not cause any damage to the film layer and further improves the accuracy of the detection results.

[0030] (3) The detection method provided by the present invention can characterize nanoscale (especially ≤20nm) film structures, and is more suitable for detection objects than ellipsometer and XRD. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a schematic diagram of the data obtained by the detection of Group A according to an embodiment of the present invention, where (a) is the full spectrum and (b) is the high-resolution spectrum of Ti2p;

[0033] Figure 2 This is a schematic diagram of the data obtained by the B group detection according to the embodiment of the present invention, where (a) is the full spectrum and (b) is the high-resolution spectrum of Ti2p;

[0034] Figure 3 This is a schematic diagram of the result after peak splitting processing of Ti2p in group A data as described in an embodiment of the present invention;

[0035] Figure 4 This is a schematic diagram of the result after peak splitting processing of Ti2p in group B data as described in an embodiment of the present invention;

[0036] Figure 5 This is the passivation film structure on the surface of the test sample obtained by comparing the peak processing results of group A and group B data as described in the embodiments of the present invention. Detailed Implementation

[0037] To make the technical means and objectives and effects of the present invention easier to understand, the embodiments of the present invention will be described in detail below with reference to specific illustrations.

[0038] It should be noted that all directional and positional terms used in this invention, such as "up," "down," "left," "right," "front," "back," "vertical," "horizontal," "inner," "outer," "top," "lower," "lateral," "longitudinal," and "center," are only used to explain the relative positional relationships and connections between components in a specific state (as shown in the accompanying drawings). They are merely for the convenience of describing the invention and do not require the invention to be constructed and operated in a specific orientation; therefore, they should not be construed as limitations on the invention. Furthermore, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated.

[0039] In the description of this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0040] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0041] like Figure 1-5 As shown, this invention discloses a method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys, comprising the following steps:

[0042] Step S1: Sample preparation and installation;

[0043] Step S2: Experimental testing. By adjusting the photoelectron energy parameters through the target material parameters, X-ray photoelectron spectroscopy is performed on the sample, and at least the full spectrum, Ti, O and C spectra are obtained.

[0044] Step S3: Data processing and analysis, charge correction of the peak position of element C, and peak fitting using high-resolution elemental spectra; determine whether the number of tests is greater than 1. If yes, proceed to step S4; otherwise, proceed to step S5.

[0045] Step S4: Determine whether the data processing results of all current test counts meet the preset conditions. If yes, proceed to step S8; otherwise, proceed to step S5.

[0046] Step S5: Determine whether the data processing results of all current test counts meet the first preset state. If yes, proceed to step S6; otherwise, proceed to step S7.

[0047] Step S6: Return to step S2 for the same region and increase the photoelectron energy;

[0048] Step S7: Return to step S2 for the same region and reduce the photoelectron energy;

[0049] Step S8: Obtain the passivation film structure on the sample surface based on the signal intensity in the data processing and analysis results.

[0050] Specifically, this example optimizes existing XPS characterization techniques by adjusting the input photoelectron energy instead of ion etching during XPS energy spectroscopy testing. A variable-energy XPS method for characterizing film structures is proposed. The structure of the passivation film on the titanium alloy surface is determined by calculating and comparing the photoelectron beam information from the excitation point of the passivation film with that emitted from the titanium alloy substrate. This allows for non-destructive testing of the passivation film structure. This testing method retains the advantages of elemental chemical state analysis in conventional XPS testing and can also obtain the passivation film structure through calculation, facilitating accurate testing and characterization of the nanoscale passivation film structure on the titanium alloy surface. It should be noted that the thickness of the passivation film on the titanium alloy surface to be tested is less than or equal to 20 nm, preferably between 3 and 20 nm. Specifically, in step S2, X-ray photoelectron spectroscopy (XPS) tests are performed on at least the full spectrum, Ti2p, O1s, and C1s. The C1s test facilitates subsequent charge correction, while the Ti2p and O1s detections help confirm the oxidation state of titanium in the film. Optionally, in step S6, the photoelectron energy is increased to twice the photoelectron energy of the previous measurement, and in step S7, the photoelectron energy is decreased to half the photoelectron energy of the previous measurement. Of course, other increasing or decreasing logic can also be used, which will not be elaborated here. In step S8, obtaining the passivation film structure of the sample surface based on the signal intensity in the data processing and analysis results refers to normalizing the signal intensity in the data processing and analysis results and outputting a schematic diagram of the corresponding passivation film structure based on the relative intensity ratio of the signals.

[0051] Specifically, the preset conditions in step S4 refer to:

[0052] In at least one test, a photoelectron signal was received only from the passivation film, and in at least one test, a photoelectron signal was received from the titanium alloy substrate.

[0053] With the above settings, XPS testing is performed at least twice, with at least one test completely detecting the interior of the passivation film and at least one test reaching the titanium alloy substrate. The photoelectron energies used in these two tests are different. By using the ratio of the passivation film signal to the metal substrate signal under different photoelectron energies, the structure of the passivation film layer on the titanium alloy surface can be determined.

[0054] Furthermore, in step S5, the first preset state refers to:

[0055] The data processing results of all tests indicate that only photoelectron signals from the passivation film were received. If the data processing results of all tests indicate that only photoelectron signals from the passivation film were received, it means that the depth of all tests performed so far is insufficient and has not reached the titanium alloy substrate. In this case, executing step S6 to increase the photoelectron energy can effectively increase the test depth so that the signal from the titanium alloy substrate can be detected in subsequent tests. When it is determined in step S5 that the first preset state is not met, it indicates that all tests performed so far can reach the titanium alloy substrate and the passivation film layer is relatively thin. In this case, executing step S7 to decrease the photoelectron energy can decrease the test depth so that the signal from the passivation film can be detected in subsequent tests.

[0056] Optionally, the photoelectron energy range used in the test is 1200~5420eV. The photoelectron energy can be adjusted by changing the parameters of the target material. By selecting a corresponding X-ray source within the aforementioned photoelectron energy range, it is possible to test the film structure of passivation films with a thickness range of 3~20nm. Within the adjustable range of photoelectron energy, test results can be obtained that show only the photoelectron signal received from the passivation film, as well as test structures that show the photoelectron signal received from the titanium alloy substrate. This facilitates accurate characterization of the passivation film structure on the surface of the titanium alloy substrate.

[0057] Specifically, step S1 includes:

[0058] Step S11: Mark the side to be tested according to XPS requirements and process the test sample;

[0059] Step S12: Fix the test sample on the sample stage and ensure that the test sample is electrically connected to the sample stage. It is important to note that during the processing of the test sample in step S11, care must be taken to keep the surface to be tested clean and free from contaminants such as oil and coolant. Suitable processing methods such as sawing can be used, and are not limited here. Furthermore, when the surface of the test sample is bombarded with X-rays, inner-shell photoelectrons (i.e., the signal to be detected in the test) are excited. For samples with poor conductivity, such as passivation films, these excited electrons are negatively charged. Their escape causes the sample surface to lose its negative charge, thus accumulating positive charge and forming a "positive charge barrier," which seriously interferes with the subsequent testing process, leading to peak broadening and distortion. In this example, ensuring electrical connection between the test sample and the sample stage can promptly neutralize the positive charge accumulated on the test sample surface, maintaining a stable and uniform potential. This ensures that the energy of the excited photoelectrons is accurately measured, resulting in a true, unbiased, high-resolution XPS spectrum.

[0060] In step S12, the test sample is adhered to the sample stage using conductive carbon-based tape, with the tape covering the edge of the test surface on the test sample. This arrangement ensures complete conductivity between the test surface and the sample stage, guaranteeing the accuracy of the test data. Optionally, the test sample can also be connected to the sample stage via snap-fit ​​or other adhesive methods, as long as conductivity between the test sample and the sample stage is maintained.

[0061] Optionally, the acquisition power range during testing is 50~600W. The acquisition power is the power applied to the X-ray target. This power allows control of the X-ray intensity, enabling the acquisition of test results with a high signal-to-noise ratio in a shorter acquisition time while ensuring the stability of the test sample.

[0062] Specifically, the sampling step size during testing is 0.05~0.2eV. The smaller the sampling step size, the higher the resolution and the more accurate the subsequent peak fitting results. However, if the sampling step size is too small, too many data points need to be collected, which can easily lead to an excessively long total acquisition time. Controlling the sampling step size within the above range can shorten the acquisition time while obtaining sufficiently accurate results.

[0063] In this example, the number of spectral samplings per test ranges from 3 to 30. Increasing the number of samplings effectively improves the signal-to-noise ratio of the spectrum, thereby reducing the impact of random noise on the test results and obtaining accurate detection results.

[0064] Example 1

[0065] Step 1: Sample pretreatment and installation: Use conductive carbon-based tape to attach the sample to the XPS sample stage. The edges of the sample surface to be tested need to be partially covered with conductive adhesive to ensure that the sample and the sample stage are fully conductive.

[0066] Step 2: XPS Experiment Test: The same area on the sample was selected, and data was collected twice using XPS. The parameters of the two collections are shown below:

[0067] (1) The photoelectron energy emitted by the target material is 1253 eV. Spectroscopy is performed using a sampling power of 150 W and a sampling step size of 0.1 eV. X-ray photoelectron spectroscopy tests are conducted on the full spectrum, Ti2p, O1s, and C1s spectra. The sampling is performed 5 times, and the obtained data is named "Group A". The data comparison graph is shown below. Figure 1 As shown;

[0068] (2) The emitted photoelectron energy of the target material is approximately 2984 eV. A sampling power of 300 W and a sampling step size of 0.1 eV were used to perform X-ray photoelectron spectroscopy tests on Ti2p, O1s, and C1s. Five sampling operations were performed, and the obtained data were named "Group B". The data comparison graph is shown below. Figure 2 As shown.

[0069] Step 3: Data Processing and Analysis: Charge correction was applied to the C element peak positions. The detected XPS signals were then subjected to peak fitting using high-resolution elemental spectra. Based on the elemental chemical states, photoelectron signals from the passivation layer and those from the metal substrate were distinguished. The structure of the surface passivation layer was determined by the ratio of the passivation layer signal to the metal substrate signal at different photoelectron kinetic energies. In this case, Ti2p was used as the target for peak fitting. The processed data for group A are shown below. Figure 3 As shown, the processed data for group B are as follows: Figure 4 As shown, the light purple area in the figure (Ti) 0 The signals are from the metal substrate, while the light blue and light orange areas represent photoelectron signals from the passivation layer. The passivation film structure exhibits a layered appearance, consisting of Ti... 4+ Layer (light blue area) and Ti 3+ The signal intensity and ratio of the two sets of data after processing are shown in Table 1. Therefore, the deduced passivation film structure of the sample surface is as follows: Figure 5 As shown. It should be noted that, Figure 5 Ti 4+ Layers and Ti 3+ The thickness comparison of the layers is used to characterize Ti in the passivation film. 4+ Layers and Ti 3+ A comparison of the actual thickness of the layers, including Ti. 0 This is only for illustrating the titanium alloy substrate and does not represent a comparison of the actual thickness of the titanium alloy substrate and the passivation film structure.

[0070] Table 1. Ratios of photoelectron intensities in different regions of the sample surface (normalized)

[0071]

[0072] Therefore, the test method provided in this example can easily and conveniently test the structural state of the passivation film on the surface of the titanium alloy substrate and characterize it. This is of great significance for optimizing and evaluating the corrosion protection performance of the material, and thus guiding process optimization and use and maintenance.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys, characterized in that, Includes the following steps: Step S1: Sample preparation and installation; Step S2: Experimental testing. By adjusting the photoelectron energy parameters through the target material parameters, X-ray photoelectron spectroscopy is performed on the sample, and at least the full spectrum, Ti, O and C spectra are obtained. Step S3: Data processing and analysis, charge correction of the peak position of element C, and peak fitting using high-resolution elemental spectra; determine whether the number of tests is greater than 1. If yes, proceed to step S4; otherwise, proceed to step S5. Step S4: Determine whether the data processing results of all current test counts meet the preset conditions. If yes, proceed to step S8; otherwise, proceed to step S5. Step S5: Determine whether the data processing results of all current test counts meet the first preset state. If yes, proceed to step S6; otherwise, proceed to step S7. Step S6: Return to step S2 for the same region and increase the photoelectron energy; Step S7: Return to step S2 for the same region and reduce the photoelectron energy; Step S8: Obtain the passivation film structure on the sample surface based on the signal intensity in the data processing and analysis results.

2. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, The preset conditions in step S4 refer to: In at least one test, a photoelectron signal was received only from the passivation film, and in at least one test, a photoelectron signal was received from the titanium alloy substrate.

3. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, In step S5, the first preset state refers to: Data processing results for all tests indicate that only photoelectron signals were received from the passivation film.

4. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, The photoelectron energies used in the tests ranged from 1200 to 5420 eV.

5. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, Step S1 includes: Step S11: Mark the side to be tested according to XPS requirements and process the test sample; Step S12: Fix the test sample on the sample stage and keep the test sample in contact with the sample stage.

6. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 5, characterized in that, In step S12, the test sample is attached to the sample stage using conductive carbon-based tape, and the conductive carbon-based tape covers the edge of the test surface on the test sample.

7. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, The power range during testing was 50~600W.

8. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, The sampling step size during testing was 0.05~0.2eV.

9. The method for detecting the passivation film structure on the surface of corrosion-resistant titanium alloys as described in claim 1, characterized in that, The number of spectral samplings per test ranges from 3 to 30.

Citation Information

Patent Citations

  • Method for detecting SEI membrane of lithium ion battery by using XPS

    CN116165234A